Multidisciplinary approach for post-acute COVID-19 syndrome: time to break down the walls. Issue 1 (8th July 2021) - Montani, David; Savale, Laurent; Beurnier, Antoine; Colle, Romain; Noël, Nicolas; Pham, Tài; Monnet, Xavier; Humbert, Marc
Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) has provoked an ongoing global pandemic of coronavirus disease 2019 (COVID-19), which has affected 130 million people worldwide and caused nearly 3 million deaths in just over 1 year [1]. In 2020, COVID-19 represented the third highest cause of death in the USA after heart disease and cancer [2], and this outbreak has led to the largest drop in life expectancy since World War II [2]. Evidence-based medical treatment of COVID-19 (anticoagulants, corticosteroids, anti-inflammatory drugs, oxygenation therapy and ventilation) [3] seems to have improved patients' outcomes, and the vast majority will recover spontaneously or after acute phase management. The importance of the COVID-19 pandemic requires us to break down the walls between medical specialties to optimise the management of patients with post-acute COVID-19 syndrome https://bit.ly/3gzqEik